Entrepreneurial Behaviour of Vegetable Growers (Indian Journal of Extension Education, 2009)
Entrepreneurial behaviour is the function of an individual’s personality characteristics (self confidence, achievement motivation, risk taking ability etc.) and environmental factors (socio-cultural factors, support system). Entrepreneurship is the response of the entrepreneur in order to earn profit by bearing the risk factor. It is centered on human skill, efficiency and strong impulse to try out the known technology with an ultimate aim to reduce the cost of production. For the present study entrepreneurial behaviour is operationalized as assemblage of personality characteristics and environmental factors contributing to transformation of physical, natural and human resources into marketable product. The present study was undertaken to analyse and understand entrepreneurial behaviour of vegetable growers.